Exchange rate misalignment and economic growth: On the possible transmission channels for emerging economies - Christian K. Tipoy; Marthinus C. Breitenbach; Mulatu F. Zerihun (Cogent Economics & Finance, 2018)
Despite the large body of work that exists on the impact of exchange rate undervaluation on economic growth, only a mere literature focuses on the potential transmission mechanisms. There are authors who consider the size of the tradable sector as the operative channel through which undervaluation impacts economic growth. This is due to poor contracting environment and market failures that are prominent in the tradable sector as bad institutions 'tax' tradables more than non-tradables. We look at this issue in this article for a set of emerging economies using annual data from 1970 to 2014. We find that the size of the tradable sector is indeed the operative channel through which undervaluation impacts growth. We have ruled out that bad institutions 'tax' tradables more than non-tradables. Our results, robust to different undervaluation indexes, highlight instead the importance of total factor productivity surge induced by an undervaluation in increasing growth.
Keywords: 330; equilibrium exchange rate; exchange rate undervaluation; economic growth; total factor productivity; transmission channel